Over-expression of the barley Phytoglobin 1 (HvPgb1) evokes leaf-specific transcriptional responses during root waterlogging - Hill, Robert D (Journal of plant physiology, 2023)
Copyright © 2023 Elsevier GmbH. All rights reserved.